Determinants of nosocomial infections and emerging antibiotic resistance in the Intensive Care Unit: A prospective evidence-based study - Pranali Patil; Amol Muthal; Jignesh Shah; Asavari Raut (Asian Pacific Journal of Tropical Medicine)
Objective: To determine the incidence, risk factors, antibiotic resistance patterns, and outcomes of various nosocomial infections in Intensive Care Unit (ICU) patients. Methods: The present prospective observational study was conducted in the multidisciplinary ICU of a tertiary care hospital for 6 months. Incidence, risk factors, and outcome parameters were calculated using Mann Whitney U test, Chi-square test, and stepwise univariate and multivariate logistic regression analysis. Results: The overall incidence of nosocomial infections was 23.5% (74/314). Ventilator-associated pneumonia was the most common infection (54.1%, 52/96), followed by catheter-related bloodstream infections (22.9%, 22/96). Stress ulcer prophylaxis (aOR 7.691, 95% CI 2.202-26.860, P=0.001), endotracheal intubation (aOR 3.251, 95% CI 1.251-8.420, P=0.015), Foley’s catheter (aOR 11.917, 95% CI 1.335-106.410, P=0.027), and ICU stay > 7 days (aOR 30.915, 95% CI 10.062-94.980, P=0.001) were statistically significant risk factors associated with nosocomial infection in ICU patients. Gramnegative bacteria showed a high degree of resistance to most of antibiotics except colistin and tigecycline. Infected group's mortality was significantly greater than the uninfected group (21.62% vs. 5.83% P<0.001) and had considerably longer ICU length of stay [21 (12) vs. 7 (4) days, P<0.001)] and duration of mechanical ventilation [20 (11) days vs. 0 (5) days, P<0.001]. Conclusions: This study highlights the high incidence rate of ventilator-associated pneumonia, with extensive drug resistance in ICU patients, highlighting the need for an optimized antimicrobial stewardship program to develop effective strategies for the management of nosocomial infections. Multifaceted interventions targeting modifiable risk factors are essential to reduce the occurences of these nosocomial infections in ICU patients.